Precision: A motor capability that defines a successful basketball player - Isaković Marko (University Educons, Faculty of Sports and Tourism, Novi Sad, 2013)
Precision, as a basic motor ability, represents, along with coordination, the least explored area of motorics. Insufficient research of this phenomenon is also true of basketball. Within it, we monitor displays of precision in the most specific of all conditions - during a basketball game. This paper represents a review of research concerning precision, with a brief critical overview of the mentioned phenomenon. Apart from the conclusions, which speak about precision as the basic motor capability (and have been presented as products of speculation and earlier findings), a review of empirical research related to situational precision has also been presented. These studies have been aimed at finding a connection between shot patterns and distance to target; goal visualisation; influence of skeleton dimension on precision. One of the goals of this paper is to point out the significance of precision of players at guard position, which could be a significant selection factor.